Nuclear and Mitochondrial Circulating Cell-Free DNA Is Increased in Patients With Inflammatory Bowel Disease in Clinical Remission - Vrablicova, Zuzana; Tomova, Kristina; Tothova, Lubomira; Babickova, Janka; Gromova, Barbora; Konecna, Barbora; Liptak, Robert; Hlavaty, Tibor; Gardlik, Roman (Frontiers in Medicine, 2020)
Background The role of cell-free DNA (cfDNA) in the pathogenesis of inflammatory bowel disease (IBD) has been recently suggested. The aim of this study was to analyze circulating cfDNA and deoxyribonuclease (DNase) activity in IBD patients in remission. Materials and methods Plasma and serum were obtained from 72 patients with Crohn’s disease and 28 patients with ulcerative colitis. Total cfDNA, nuclear DNA (ncDNA), mitochondrial DNA (mtDNA) and DNase activity were measured. Results IBD patients showed higher levels of both ncDNA and mtDNA compared to healthy controls. Concentration of ncDNA was higher in males compared to females, including patients and healthy controls. However, unlike males higher amount of ncDNA was found in female IBD patients compared to healthy controls. DNase activity was significantly lower in male IBD patients compared with healthy controls. In addition, there was a negative correlation between DNase activity and ncDNA levels in male IBD patients. Conclusions Herein we present increased amount of circulating ncDNA and mtDNA in IBD patients in remission. Thus, unlike total cfDNA, circulating ncDNA and mtDNA might not represent the optimal biomarkers of disease activity. This is also the first report on sex difference in circulating ncDNA levels, possibly associated with lower DNase activity in males.